Development and validation of an ADDIE-based jobsheet as procedural scaffolding for vocational electrical practice - Siswo Wardoyo; Deva Adelya Prestanty; Suhendar Suhendar; Mohd Ridhuan Mohd Jamil; Mohammad Fatkhurrokhman (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2026)
Vocational electrical learning requires students to transform technical concepts into safe, ordered, and assessable workshop performance. This study developed and validated an ADDIE-based electrical lighting installation jobsheet as a form of procedural scaffolding for Grade XI students at an Indonesian vocational school. A research-and-development design was implemented using the ADDIE stages of analysis, design, development, implementation, and evaluation, with a one-group development trial. Data were collected through classroom observation, a teacher interview, expert validation, student-response questionnaires, and diagnostic, formative, and summative assessments. Three media experts, three material experts, and 23 students participated. The jobsheet was produced in printed and digital formats and covered five practice units: single-switch installation, series-switch installation, two-way switch installation, distribution-board lighting installation for a simple building, and light-sensor-based lighting installation. Expert validation indicated high feasibility in terms of media quality (M = 3.83/4.00) and material quality (M = 3.84/4.00), while the student response was positive (M = 3.49/4.00). Learning scores increased from diagnostic assessment (M = 47.61) to summative assessment (M = 85.65), with high normalised gain (g = 0.73), a very large paired effect size (Cohen’s dz = 3.02), and 82.61% summative mastery. The findings indicate that a systematically designed jobsheet can connect curriculum outcomes, occupational safety, practical procedures, and assessment evidence. Because the implementation employed a one-group development trial, the findings should be interpreted as evidence of instructional feasibility and associated learning improvement rather than causal effectiveness. The study contributes a low-cost, competency-aligned practical learning resource for vocational electrical education; however, further controlled and multi-site studies are required to verify retention and practical-skill transfer.